School wars. The battle for Britain's education - Benn, Melissa (London, 2011)
"School Wars tells the story of the struggle for Britain’s education system. Established during the 1960s and based on the progressive ideal of good schools for all, the comprehensive system has over the past decades come under sustained attack from successive governments.